PEMIKIRAN HADIS SHÂH WALÎ ALLAH AL-DAHLAWÎ TENTANG METODE PEMAHAMAN HADIS - Fatichatus Sa'diyah (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2019)
The problem of understanding the hadith of the Prophet is an urgent question to discuss. This stems from the reality of the hadith as the second source of Islamic teaching after the Quran which in some respects is different from the Quran. One possible way is to conduct a study on the method of understanding the hadith of Shah Walî Allah al-Dahlawî. In this study, it will be elaborated on the method of understanding the hadith based on their forgetting. The results of this study show that epistemologically, the method of understanding hadith according to al-Dahlawî is, among others; the understanding of the hadith based on its validity (knowing its meaning, thus its legal content, ‘illat, harmony, and conditions), the solution of the opposite hadith, and the understanding of the hadith based on historical facts. Ontologically, the method of understanding al-Dahlawî’s hadith is: the hadith is understood based on the position of the Prophet divided into two parts (tablîgh and ghayr al-tablîgh), and the hadith is also understood based on the secrets contained in the text of the hadith. Such al-Dahlawî’s thinking on the method of understanding the hadith has several implications; First, the understanding of the hadith offered opens up the possibility of developing scholars insights later, in which they adopt the same approach as al-Dahlawî. Second, the applications and examples presented by al-Dahlawî have much to do with fiqh. He was a scholar who was able to reconcile the hadith and fiqh, whose thoughts from his works are the answer to the turmoil of thought and the sect that occurred in his time in India. Kata Kunci: Hadis, Hadith Thought, Shâh Walî Allah al-Dahlawî, the method of understanding the hadith